Information Literacy and Library Education: Exploring Dimensions in Librarian’s Role - Sharma, Sangeeta (Journal of Information and Knowledge, 2008)
The article deals with the understanding of information and information needs and status of users. How information literacy and library user education are changing and demanding in the age of World Wide Web and electronic collection has been explored. The article highlights current information networking practices in education centers. Librarian and staff’s role as intermediary and facilitator has been analyzed and presented in the perspectives of information literacy. Information literacy has distinct place in the context of online learning and libraries. Need of information literacy in the perspectives of Digital libraries and World Wide Web sites and page persistence and Electronic publishing have been discussed.